2023
DOI: 10.1111/ijcs.12962
|View full text |Cite
|
Sign up to set email alerts
|

Four decades of negative word‐of‐mouth and negative electronic word‐of‐mouth: A morphological analysis

Abstract: Customers voice their negative brand experiences to their family and friends in the form of negative word‐of‐mouth (NWOM). Web 2.0 enables the sharing of NWOM in electronic format on various social media sites, online customer review forums, and blogs, which is known as negative electronic word‐of‐mouth (NeWOM). Researchers need to study the spread of NWOM/NeWOM to prevent adverse consequences for companies and suggest an optimal response for its redressal. Existing literature review studies have focused on wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 216 publications
0
1
0
Order By: Relevance
“…They have performed a meta‐analysis and using two‐stage structural equation model found that message characteristics (perceived informativeness, message quality), and source characteristics (source trustworthiness and source expertise) had a profound impact on eWOM adoption. On the similar lines, Ribeiro and Kalro (2023) conducted a review on negative eWOM using morphological analysis. The review mentioned areas which impact negative eWOM like receiver and sender characteristics, brand, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…They have performed a meta‐analysis and using two‐stage structural equation model found that message characteristics (perceived informativeness, message quality), and source characteristics (source trustworthiness and source expertise) had a profound impact on eWOM adoption. On the similar lines, Ribeiro and Kalro (2023) conducted a review on negative eWOM using morphological analysis. The review mentioned areas which impact negative eWOM like receiver and sender characteristics, brand, and so forth.…”
Section: Discussionmentioning
confidence: 99%